Early Childhood Education Effect on Sustainable Development and Developmental Education - Mardomi, Reyhaneh; Mardomi, Somayeh (Early Childhood Research Journal (ECRJ), 2023)
Early Childhood Education (PAUD) plays an important role in achieving sustainable development at a young age. In other words, Education for Sustainable Development can be considered as educational development to utilize education and achieve sustainability in PAUD. The aim of this research is to find out children from low-income families about their interest in going to school. This research method uses literacy studies. The results of this research are that the low interest of children in developing countries, especially children whose parents have low incomes, to continue their studies is a challenge for the education system. Therefore, the education system as the main component should be able to meet special needs to empower individuals not only to acquire knowledge but also to develop awareness of values and virtues, in making decisions, and exploiting their potential in all areas of life. and work for individuals and society. The overall impact of the studies in these SDGs is attention to the role of Education in Sustainable Development among young children and developmental education with a focus on taking a child-oriented perspective, which can be extended to all young learners around the world.